Characterisation and evaluation of columnar basalt geoheriatge in Thailand: Implication for geotourism management in post-quarring area - Singtuen, Vimoltip; Anumart, Apussorn (Quaestiones Geographicae, 2022)
Late Cenozoic basaltic rocks in Nang Rong Columnar Jointed Basalts in southern Khorat Plateau are among the greatest columnar basalts in Thailand as famous geoheritage sites. This work aims to characterize and evaluate the post-quarrying area by field investigation, petrography, geochemistry, and geological engineering. A petrographical study determines these basalts as olivine basalts, presenting porphyritic texture with olivine microphenocryst. Geochemical characteristics indicate these basalts were alkaline basalt generated from alkaline sodic magma series within the continental plates. In addition, columnar jointed basalt presents compressive strength and point load strength index higher than platy basalt with a higher percentage of alteration. Local authorities enhance people in the area to develop and promote their georesources through touristic activities. This geoheritage demonstrates high geology and tourism management values; thus, it could be the prototype of the post-quarrying geosite of Thailand.